2016
DOI: 10.1515/msr-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quadrature Signal Estimation Method for a Planar Capacitive Incremental Displacement Sensor

Abstract: This paper presents a novel phase-shift arctangent (PSA) interpolation method to improve the measurement accuracy of a planar capacitive incremental displacement sensor. Signals of planar capacitive micro-sensors acquire waveform errors, including sensitivity differences and phase-shift errors, because of static errors and dynamic disturbances. In the proposed PSA scheme, such errors are removed completely by loading a particular arctangent function. Moreover, measuring efficiency of the proposed planar capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In a proposed phase shift arctangent (PSA), quadrature signal estimation method for a planar capacitive incremental displacement sensor, electrode width was set as four-times the gap distance to increase measuring sensitivity [ 15 ]. Experiment results indicated that the effects of static errors and dynamic disturbances have been mostly removed, however, waveform deformation errors remained.…”
Section: Sensor Model Against Fringe Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a proposed phase shift arctangent (PSA), quadrature signal estimation method for a planar capacitive incremental displacement sensor, electrode width was set as four-times the gap distance to increase measuring sensitivity [ 15 ]. Experiment results indicated that the effects of static errors and dynamic disturbances have been mostly removed, however, waveform deformation errors remained.…”
Section: Sensor Model Against Fringe Effectsmentioning
confidence: 99%
“…The X - Y displacement information as D X and D Y are obtained by a particular arctangent function as shown in Equations (11) and (12). Effects of some inevitable roll, yaw, and pitch angular errors would be well balanced [ 5 , 15 , 16 ].…”
Section: Sensor Model Against Fringe Effectsmentioning
confidence: 99%
“…The resolution of the system is 0.308 µm [14]. Subsequently, the team also proposed a novel phase-shifting arctangent interpolation method to improve the measurement efficiency of the planar capacitive sensor, which can reduce the waveform error from 4% to 1.72% [15]. Capacitive displacement sensors can achieve µmor even nm-level measurement accuracy in a small measurement range, but the dielectric constant between its two electrodes is easily affected by environmental factors, so capacitive sensors are not suitable for use in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent displacement error caused by fringe effects was 237 µm, and the equivalent displacement interpretation error was 141 µm. Moreover, a novel phase-shift arctangent interpolation method was utilized to decrease waveform errors from 4% to 1.72% [17]. A planar position sensor based on mono sensing electrode and hybrid-frequency excitation was proposed in [18].…”
Section: Introductionmentioning
confidence: 99%